Improvement of the Targeting of Radiolabeled and Functionalized Liposomes with a Two-Step System Using a Bispecific Monoclonal Antibody (Anti-CEA × Anti-DTPA–In) - Rauscher, Aurore; Frindel, Mathieu; Rajerison, Holisoa; Gouard, Sébastien; Maurel, Catherine; Barbet, Jacques; Faivre-Chauvet, Alain; Mougin-Degraef, Marie (Frontiers in Medicine, 2015)
This study proposes liposomes as a new tool for pretargeted radioimmunotherapy (RIT) in solid tumors. Tumor pretargeting is obtained by using a bispecific monoclonal antibody (BsmAb, anti-CEA x anti-DTPA-In) and pegylated radioactive liposomes containing a lipid-hapten conjugate (DSPE-PEG-DTPA-In). In this work, the immunospecificity of tumor targeting is demonstrated both in vitro by fluorescence microscopy and in vivo by biodistribution studies. Methods: Carcinoembryonic antigen (CEA)-expressing cells (LS174T) were used either in cell culture or as xenografts in nude mice. Doubly fluorescent liposomes or doubly radiolabeled liposomes were respectively used for in vitro and in vivo studies. In each case, a tracer of the lipid bilayer (rhodamine or indium-111 (111In)) and a tracer of the aqueous phase (fluorescein or iodine-125 (125I)) were present. The targeting of liposomes was assessed with BsmAb for active targeting or without for passive targeting. Results: Data obtained with the lipid bilayer tracer showed a fluorescent signal on cell membranes two to three times higher for active than for passive targeting. This immunospecificity was confirmed in vivo with tumor uptake of 7.5 ± 2.4 % ID/g (percentage of injected dose per gram of tissue) for active targeting versus 4.5 ± 0.45 % ID/g for passive targeting (p = 0.03). Regarding the aqueous phase tracer, results are slightly more contrasted. In vitro, the fluorescent tracer seems to be released in the extracellular matrix, which can be correlated with the in vivo data. Indeed, the tumor uptake of 125I is lower than that of 111In: 5.1 ± 2.5 % ID/g for active targeting and 2.7 ± 0.6 % ID/g for passive targeting, but resulted in more favorable tumor/organs ratios. Conclusion: This work demonstrated the tumor targeting immunospecificity of DSPE-PEG-DTPA-In liposomes by two different methods. This original and new approach suggests the potential of immunospecific targeting liposomes for the RIT of solid tumors.